PENGARUH TERAPI BEKAM TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DUSUN TAMBAK REJO DESA GAYAMAN MOJOKERTO - Yufi Aris Lestari; Aris Hartono; Ucik Susanti (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2017)
Hypertension usually has no symptoms. That is why high blood pressure is called the silent killer. Hypertension that experienced by the public has been increase because most of them breaking treatment due to the high cost of treatment. One of the efforts made to resolve the issue with a non pharmacological therapy but with cupping therapy. This study aimed to determine the effect of cupping therapy to changes in blood pressure on the patients with hypertension.This reseach used design is Quasy experiment Pre Test - Post Test Control Group. The population is patients with hypertension in the Tambak Rejo Village Gayaman District Mojokerto Regency were 28 people, sample in this study are 28 respondents and divided into two groups: experiment and control groups, with total sampling technique. The data obtained through observation sheet blood pressure were analyzed descriptively to determine differences in mean changes of blood pressure.The result show that there are differences between the mean of blood pressure on Pretest and Post Test. The experiment group average value of SBP change is -28.57 mmHg, DBP -10.71 mmHg and MAP -16.66 mmHg. In the otherside control group SBP 8.57 mmHg, DBP 3.57 mmHg and MAP 5.23 mmHg.The reseach show that there is significant effect of cupping therapy for the patient with hypertension. And cupping therapy can be use as alternative therapy for patient with hypertension.